Blood Rheology in Marine Mammals - Castellini, Michael; Baskurt, Oguz; Castellini, Judith M.; Meiselman, Herbert J. (Frontiers in Physiology, 2010)
The field of blood oxygen transport and delivery to tissues has been studied by comparative physiologists for many decades. Within this general area, the particular differences in oxygen delivery between marine and terrestrial mammals has focused mainly on oxygen supply differences and delivery to the tissues under low blood flow diving conditions. Yet, the study of the inherent flow properties of the blood itself (hemorheology) is rarely discussed when addressing diving. However, hemorheology is important to the study of marine mammals because of the critical nature of the oxygen stores that are carried in the blood during diving periods. This review focuses on the essential elements of hemorheology, how they are defined and on fundamental rheological applications to marine mammals. While the comparative rationale used throughout the review is much broader than the particular problems associated with diving, the basic concepts focus on how changes in the flow properties of whole blood would be critical to oxygen delivery during diving. This review introduces the reader to most of the major rheological concepts that are relevant to the unique and unusual aspects of the diving physiology of marine mammals.